Identification of potential 'lifestyle-responsive' epigenomic biomarkers in healthy women aged 18–40. (4th July 2018) - Thunders, Michelle; Chinn, Victoria; Bilewitch, Jaret; Stockwell, Peter
Abstract: Context: Human health is complex and multifaceted; there is a need for biomarkers that reflect the multidimensional nature of health. Objective: To identify potential epigenomic biomarkers of health in women aged 18–40 participating in a six-month lifestyle intervention, next level health. Materials and methods: Methylation data were obtained by reduced representation bisulphite sequencing of 21 female intervention participants as well as three non-participants. The Differential Methylation Analysis Package (DMAP) was used to investigate inter- and intra-individual variability and to identify potential targets of transient epigenetic control in the population studied. Results: Eleven genes were identified as significantly differentially methylated post- intervention in all 21 participants. 1884 genomic locations were found to be differentially methylated amongst the total female population studied representing potential epigenomic biomarkers. Conclusions: The ability to demonstrate epigenetic changes arising from a lifestyle intervention can provide key information on the relationship between gene regulation, human behaviour and health.